"Siregarization" of Kahiyang-Bobby: Inter-Indigenous Marriage, Patrilinealization or For the sake of Na Tolu? - Saptomo, Ade; APHA, Journal Manager (Jurnal Hukum Adat Indonesia, 2017)
This paper is the result of an analysis of the marriage event of two people that have different ethnicities, Javanese and Batak, and the kinship system, Parental and Patrilinieal. In the marriage process which was carried out according to the patrilineal kinship sistem followed by giving the clan title from Batak. The question, is such marriage an interadat, or patrilinealisation, dalihan na tolu? To answer it, socio-antro legal research was done by implementating the complementary approaches, adat law science and legal anthropology. The result, the marriage isn’t named antaradat, the mentioned marriage has been legal according to the adat Batak in which the one party received one of the clans in the Batak ethnic so that the marriage is the endogamy marriage of the ethnic and the exogamy of the clan and keep on dalihan na tolu.